Kinerja Badan Kepegawaian Dan Diklat Daerah Dalam Pelayanan Administrasi Pegawai Negeri Sipil Di Kabupaten Bolaang Mongondow Timur. - MOKOAGOW, MOH RIDHA; LENGKONG, FlORENCE DAYCY; Laloma, Alden (Sam Ratulangi University, 2014)
Based on regulation number 43 of 1999 and Section 34A of Presidential Decreenumber 150 of 2000 that the Regional Employment Board is a device that has the main duty toassist the Regional Employment Development Officer in implementing the Regional Civil Servicemanagement, administrative services including organizing a Regional Civil Servants. The purposeof this study was to determine how the performance Personnel Board and Regional TrainingBolaang East Mongondow in the Civil Service administrative services in the area. This researchuses a qualitative method with the number of informants as many as 12 people consisting ofofficials and employees implementing the Personnel Board and Regional Training Bolaang EastMongondow as many as 6 people by using purposive and civil servants in some sectors in thegovernment environment as much Bolaang East Mongondow 6 people with random techniques.From the results of existing research, the performance Personnel Board and Regional TrainingBolaang East Mongondow in the Civil Service administrative services from the aspects ofeffectiveness, efficiency, responsiveness and transparency can be considered quite good, but itwould be better if it improved again in order to achieve effective and efficient .